Partial discharge behaviours within a void-dielectric system under square waveform applied voltage stress - Illias, Hazlee Azil; Tunio, M.A.; Bakar, Ab Halim Abu; Mokhlis, Hazlie; Chen, G. (Institution of Engineering and Technology (IET), 2014)
There are many factors, which influence the behaviours of partial discharge (PD) within a void located in a solid dielectric material. One of the important factors is the waveform of the applied voltage on the electrode of a system, such as its amplitude and frequency. In this study, a two-dimensional axial-symmetric model of a cylindrical void in polyethylene layers has been developed using finite element analysis software. The model was used to simulate PD activity in the void under square waveform applied voltage under different amplitudes of the voltage. The model has considered the effect of charge propagation along the void surface during a PD occurrence. The obtained simulation results were compared with the measurement results reported from previous literature to validate the PD model that has been developed in this work. It was found that the simulation and measurement results are within reasonable agreement with only slight disagreement. From the comparison, critical parameters from the model that affect PD behaviours under square waveform applied voltage were found to be the electron generation rate and the inception, extinction and critical charge propagation fields. These findings may increase an understanding of PD behaviours within a void in a dielectric material under square waveform applied voltage, which is important for insulation diagnosis.